Magnetotelluric imaging of the Mérida Andes and surrounding areas in Venezuela. Issue 3 (1st June 2020) - Cruces-Zabala, J; Ritter, O; Weckmann, U; Tietze, K; Schmitz, M
SUMMARY: The Caribbean and South American tectonic plates bound the north-eastwards expulsion of the North Andean Block in western Venezuela. This complex geodynamic setting resulted in the formation of major strike-slip fault systems and sizeable mountain chains. The 100-km-wide Mérida Andes extend from the Colombian/Venezuelan border to the Caribbean coast. To the north and south, the Mérida Andes are bound by hydrocarbon-rich sedimentary basins. Knowledge of lithospheric structures, related to the formation of the Mérida Andes, is limited though, due to a lack of deep geophysical data. In this study, we present results of the first broad-band magnetotelluric profile crossing the Mérida Andes and the Maracaibo and Barinas–Apure foreland basins on a length of 240 km. Geoelectrical strike and dimensionality analysis are consistent with 1-D or 2-D subsurface structures for the sedimentary basins but also indicate a strong 3-D setting for the Mérida Andes. Using a combination of 2-D and 3-D modelling we systematically examined the influence of 3-D structures on 2-D inversions. Synthetic data sets derived from 3-D modelling allow identification and quantification of spurious off-profile features as well as smoothing artefact due to limited areal station coverage of data collected along a profile. The 2-D inversion models show electrically conductive basins with depths of 2–5 km for the Barinas-Apure and 2–7 km for the Maracaibo basins. A number of resistive bodies within the Maracaibo basin could be related to active deformation causing juxtaposition of older geological formations and younger basin sediments. The most important fault systems of the area, the Boconó and Valera Faults, cross-cut the Mérida Andes in NE–SW direction along its strike on a length 400 km and N–S direction at its centre on a length 60 km, respectively. Both faults are associated with subvertical zones of high electrical conductivity and sensitivity tests suggest that they reach depths of up to 12 km. A sizeable conductor at 50 km depth, which appears consistently in the 2-D sections, could be identified as an inversion artefact caused by a conductor east of the profile. We speculate the high conductivity associated with the off-profile conductor may be related to the detachment of the Trujillo Block. Our results partially support the 'floating orogen hypothesis' developed to explain the geodynamic evolution of western Venezuela and they highlight the relevance of the Trujillo Block in this process.